Kapasitas Momen Maksimum Pondasi Tiang Pendek Silindris Akibat Beban Lateral pada Tanah Lempung dengan Metode Kurva P-Y - Andriani, Utari Wessy; Suhartatik, Ita (Department of Civil Engineering, Diponegoro University, 2013)
For a certain structure, lateral loads are more dominant than vertical loads. A foundation with a lateral load is due to overturning force relying on good contact between the pile and the soil. This research is about a wll foundation or a rigid pile due to lateral loads on clay, using a cylinder pile model 85 mm diameter with various ratio length of pile (L/D) = 4 to 5 and ratio lies of load (e/L)=1,2 and 4. The results are: (1) Increasing ratio lies of load (e/L) so decreasing maximum lateral load (Pmax) can be supported by pile foundation, and the increasing maximum displacement and maximum moment. (2) Maximum deflection occur at surface soil with rotation point at average L/3 from bottom of pile, and maximum moment occur at L/3 from surface soil. (3) The maximum moment of result laboratory test are smaller than the maximum moments of result numeric analysis with consideration value between 1 to 1.5. These differences are caused by the influence of soil processing during laboratory test so they can influence the value of soil parameters. Based on consideration value, the prediction of maximum moment capacity by curve p-y method can be used in the design of pile foundation by considering the use of safety factor=2.